From Marcus Welby, M.D. to The resident: The changing portrayal of physicians in TV medical dramas - Irene CAMBRA BADII et al (Revista de Medicina y Cine / Journal of Medicine and Movies, 2018)
Over the years, the way medical dramas represent health professionals has changed. When the first medical dramas were broadcasted, the main characters were good, peaceful, intelligent, competent, empathic, and successful physicians. One of the most famous, even outside the US, was Marcus Welby M.D. (1969-1976) of David Victor –which this year marks 50 years since its first emission. This depiction began to change in the mid-1990s. While maintaining the over positive image of medical doctors, TV series started to put more emphasis on their negative characteristics and difficulties in their interpersonal relationships, such as ER (TV) by Michael Crichton (United States) and House MD (TV) by David Shore (United States). In these series, physicians were portrayed as arrogant, greedy, and adulterous, and their diagnostic and therapeutic errors were exposed. The last two series are The Good Doctor (TV) by David Shore (United States), with a resident of surgery with autism and Savant syndrome, and The Resident (TV) by Amy Holden Jones, Hayley Schore and Roshan Sethi (United States), where serious institutional problems appear. These series can be useful as a method to discuss medical ethics through positive or negative examples, and also help to represent changes in the image of physicians in recent decades, discussing the reasons for these changes.